2022
DOI: 10.3390/polym14204410
|View full text |Cite
|
Sign up to set email alerts
|

The Use of 3D Optical Coherence Tomography to Analyze the Architecture of Cyanobacterial Biofilms Formed on a Carbon Nanotube Composite

Abstract: The development of environmentally friendly antifouling strategies for marine applications is of paramount importance, and the fabrication of innovative nanocomposite coatings is a promising approach. Moreover, since Optical Coherence Tomography (OCT) is a powerful imaging technique in biofilm science, the improvement of its analytical power is required to better evaluate the biofilm structure under different scenarios. In this study, the effect of carbon nanotube (CNT)-modified surfaces in cyanobacterial biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 74 publications
3
11
1
Order By: Relevance
“…Significantly lower biofilm porosity values (∼0.1 in shallow mode) were obtained from the 3D OCT images using BISCAP. Those values, although very low, are closer to the porosities reported in Romeu et al (2022) (also from 3D OCT image processing), ranging between 0.2 and 0.4. Those differences might be due to the biofilm structure or the conceptual interpretation of porosity calculations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Significantly lower biofilm porosity values (∼0.1 in shallow mode) were obtained from the 3D OCT images using BISCAP. Those values, although very low, are closer to the porosities reported in Romeu et al (2022) (also from 3D OCT image processing), ranging between 0.2 and 0.4. Those differences might be due to the biofilm structure or the conceptual interpretation of porosity calculations.…”
Section: Discussionsupporting
confidence: 85%
“…Using these arrays, it is possible to calculate several biofilm structural parameters. Consistently with Narciso et al (2022) and Romeu et al (2022) , biofilm thickness ( L F ) is calculated as follows: 0 1 1 0 1 1. …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the biovolume of biofilms formed on both surfaces was calculated for incubation day 42 ( Figure 6 a). This parameter provides an estimate of the biomass in the biofilm (µm 3 ) per area of the region of interest (mm 2 ) [ 31 ]. Results showed that the biofilms formed on G5/PDMS had significantly lower biovolume than those developed on the control surface (on average, 1.80 × 10 8 µm 3 ·mm −2 for PDMS versus 8.89 × 10 7 µm 3 ·mm −2 for G5/PDMS; p ≤ 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…In order to further assess biofilm architecture, for the last sampling day, biofilm porosity and biofilm biovolume were determined as described by Romeu et al [ 31 ]. The percentage of biofilm porosity corresponds to the ratio between the volume of non-connected pores and the total biofilm volume, whereas biovolume pertains to the total biofilm volume per area of the region of interest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation